THE CONCERT IN THE (GERMAN) DRAWING ROOM. CONCERNING THE THEME OF MEDIAN QUALITY OF THE ART OF MUSIC / КОНЦЕРТ В (НЕМЕЦКОЙ) ГОСТИНОЙ. К ТЕМЕ О МЕДИАЛЬНОСТИ МУЗЫКАЛЬНОГО ИСКУССТВА - NOVAK N. / НОВАК Н. (Наука телевидения)
On the basis of the data about the Federal Republic of Germany the article examines the measures taken by theater ad concert organizations with the aim of expanding the contingent of audiences by means of reclaiming virtual space. It is known that from the moment of the formation of the performing musician critics pay attention to many things, including the artist’s outward appearance. The authenticity of the musician’s image is one of the most important constituent parts of the concert ritual. Proposals of the leading music ensembles, such as the Berlin Philharmonic or the Viennese State Opera, regarding dissemination of production within the framework of online broadcasts are perceived by the author in the vein of preservation of the “concert-like” atmosphere. In such a case “visitation of the listener in his or her home” is not only the attempt to go along with time. In light if research works about the multimodality of perception the availability of visual irritants leads to the rise of its quality and, consequently, the ratings of classical academic music in the eyes of the listener. The text of the article consists of four parts. After the enumeration of examples of visualization in the sphere of the art of music there is a description of scenarios offered by well-known concert ensembles and theater groups. A comparative overview of the research products which are the most interesting from the point of view of the author, devoted to the spectacular component of perception of music, presents the article’s central element. The conclusions draw upon the theme of new challenges appearing before traditional musicology, including, within the framework of research of the art of performance. In the latter it is, obviously, not sufficient to rely on the material contained on physical carriers, i.e. it becomes necessary to master new means of recording.